HOW TO PLAN, HANDLE, ANALYSE AND INTERPRET NARRATIVES, ACCORDING TO THE QUALITATIVE-UNDERSTANDING APPROACH? - Toscano, Maria de Fátima (Cadernos de Educação Tecnologia e Sociedade, 2019)
This paper derives from our PhD research in Sociology on socio-identitarian requalification processes (processos de requalificação socio-identitária, henceforth PRSI) of Portuguese women who migrated to the Basque Country (San Sebastian area). To this end, we co-composed 31 exemplary case accounts, following the question: â€œWhat are the logics of action and what identitarian strategies are adopted by women who, facing the social experience of disqualification, engage in their â€˜socio-identitarian requalificationâ€™?â€ We focus and organize this paper on the exposition of the main procedures and specific forms of the qualitative analysis, as we applied it at the â€˜the processes of socio-identitarian requalification (PRSI) - how we called, since 2008, the analytical-understanding model of social trajectories of requalification from poverty conditions. (cf. Toscano 2015, 2017, 2018). So, in this paper, we explain in depth how we organize the 4 methodological acts which compose this 'analytical-understanding model processes of socio-identitarian requalification' that we have been developing since 2008 in our analysis of trajectories for social change ('leaving' so called poverty conditions). Therefore, after a brief mention of the Tool-Problematics, which constitutes the base for our research, in point 1.1 (1st act: theoretical-conceptual-epistemological roots), we focus on specific procedures, such as: - point 2: justifying the co-composition of accounts: operationalizing principles, procedures and criteria for the selection of exemplary cases and composition of narratives (2nd act, steps 2-3); - point 3: planning and co-composing the biographical process (2nd act, Steps 4a-4b; 6 stages); - point 4 (3rd act), 1st level of theorization: writing down speech through transcription-translation (step 5; stages 7-8) and transposition-rearrangement (analysis units, operation mode, discursive levels, account axes, rules/kinds of annotation - steps 6-7, stages 9-12); - point 5 (4th act), 2nd level of theorization: interpretation and theorizing composition in emergence (steps 8-9, stages 13-14, 7 operations); and finally, point 6, brief conclusions..